The Role of Job Satisfaction and Organizational Commitment on Turnover Intentions of Accounting Professionals in Big 3 Auditing Firms in the Philippines with Moderating Effect of Leader-member Exchange - Tubay, Jerwin B. (International Review of Management and Marketing, 2019)
The main purpose of this paper is to determine whether job satisfaction, both intrinsic and extrinsic; as well as organizational commitment, both affective, continuance and normative; would predict the turnover intention of Certified Public Accountants working in Big 3 auditing firms in the Philippines. The effect are also studied whether it will be moderated by leader-member exchange. The impact of the predictors were determined using multiple regression and moderated multiple regression was used to test the moderating effects. The results showed that only extrinsic job satisfaction has a significant negative effect on turnover intentions. Leader-member exchange on the other hand moderated the effect of normative commitment and continuance commitment on turnover intentions. Recommendations based on the conclusion as well as the limitations of the study were also discussed. Keywords: Turnover intention; Job satisfaction; Organizational commitment; Accounting firms JEL Classifications: M1, M4, M5 DOI: https://doi.org/10.32479/irmm.7632